Mitochondrial translation factors of Trypanosoma brucei: elongation factor‐Tu has a unique subdomain that is essential for its function. Issue 4 (30th September 2013) - Cristodero, Marina; Mani, Jan; Oeljeklaus, Silke; Aeberhard, Lukas; Hashimi, Hassan; Ramrath, David J. F.; Lukeš, Julius; Warscheid, Bettina; Schneider, André
Summary: Mitochondrial translation in the parasitic protozoan Trypanosoma brucei relies on imported eukaryotic‐type tRNAs as well as on bacterial‐type ribosomes that have the shortest known rRNAs. Here we have identified the mitochondrial translation elongation factors EF‐Tu, EF‐Ts, EF‐G1 and release factor RF1 of trypanosomatids and show that their ablation impairs growth and oxidative phosphorylation. In vivo labelling experiments and a SILAC‐based analysis of the global proteomic changes induced by EF‐Tu RNAi directly link EF‐Tu to mitochondrial translation. Moreover, EF‐Tu RNAi reveals downregulation of many nuclear encoded subunits of cytochrome oxidase as well as of components of the bc1‐complex, whereas most cytosolic ribosomal proteins were upregulated. Interestingly, T. brucei  EF‐Tu has a 30‐amino‐acid‐long, highly charged subdomain, which is unique to trypanosomatids. A combination of RNAi and complementation experiments shows that this subdomain is essential for EF‐Tu function, but that it can be replaced by a similar sequence found in eukaryotic EF‐1a, the cytosolic counterpart of EF‐Tu. A recent cryo‐electron microscopy study revealed that trypanosomatid mitochondrial ribosomes have a unique intersubunit space that likely harbours the EF‐Tu binding site. These findings suggest that the trypanosomatid‐specific EF‐Tu subdomain serves as an adaption for binding to these unusual mitochondrial ribosomes.